Rapid Mining of Candidate Genes for Verticillium Wilt Resistance in Cotton Based on BSA-Seq Analysis - Cui, Yanli; Ge, Qun; Zhao, Pei; Chen, Wei; Sang, Xiaohui; Zhao, Yunlei; Chen, Quanjia; Wang, Hongmei (Frontiers in Plant Science, 2021)
Cotton is a globally important cash crop. Verticillium wilt (VW), commonly known as “cancer” of cotton, is damaging to cotton production around the world, as it seriously reduces yield and fiber quality. Here, we performed a BSA-seq strategy using an F2:3 segregation population to identify candidate loci involved in VW resistance. Two QTLs (qvw-D05-1 and qvw-D05-2) related to VW resistance in cotton, were identified using two resistant-susceptible bulks from the F2 separate group constructed by crossing the resistant cultivar ZZM2 with the susceptible cultivar J11. A total of 30 stop-lost sites and 42 stop-gained sites, which included 17 genes in total were screened in the qvw-D05-2 region using SnpEff analysis. During further analysis of transcriptome data, we found that the expression levels of Ghir_D05G037630 differed significantly in different periods after infection with V. dahliae. We named the gene GhDRP. During its sequence analysis, we found that the change of one base in GhDRP resulted in one amino acid difference between ZZM2 and J11. The silenced plants became more susceptible to V. dahliae than the control, according to VIGS technology, suggesting that GhDRP may be involved in the process of resisting V. dahlia infection. This study provided a method for rapidly mining quantitative trait loci and screening candidate genes, and thus has enriched genomic site information and gene resources for the molecular breeding of disease resistance in cotton.